Efficacy and Safety of Aspirin 162 mg for Preeclampsia Prophylaxis in High-Risk Patients - Ayyash, Mariam; Goyert, Gregory; Garcia, Robyn; Khangura, Raminder; Pitts, D'Angela; Jacobsen, Gordon; Shaman, Majid (American Journal of Perinatology, 2023)
Objective The aim of this study was to compare the safety and efficacy of aspirin 162 mg to the standard recommended dose of 81 mg for preeclampsia prevention.Study Design A retrospective cohort study of patients at risk for preeclampsia who delivered between January 2013 and December 2020 at Henry Ford Health was performed. Patients were divided into three groups: a no aspirin group, a group treated under an 81 mg aspirin preeclampsia prophylaxis protocol, and a group treated under a 162 mg protocol. Univariate and multivariable logistic regression analyses compared rates of preeclampsia and secondary outcomes between groups. Clinical side effects traditionally associated with aspirin use were also assessed.Results Of 3,597 patients, 2,266 (63%) were in the no aspirin group, 944 (26%) were in the 81 mg group, and 387 (11%) were in the 162 mg group. The rate of preeclampsia was significantly lower in the 162 mg group (10.1%, odds ratio, 0.68; 95% confidence interval, 0.46–0.99) compared with the 81 mg group (14.2%). The rate of preeclampsia was identical in the no aspirin and 81 mg groups. The rate for postpartum hemorrhage, postpartum hematoma, and intraventricular hemorrhage of the newborn were not significantly different between patients in the 162 and 81 mg groups.Conclusion We observed a significantly lower rate of preeclampsia in high-risk patients who were treated with the 162 mg dose of aspirin for preeclampsia prophylaxis, and bleeding complications were not seen with the higher dose. Our study suggests that aspirin 162 mg may be considered for prophylaxis in patients at high risk for preeclampsia.Key Points
Keywords: preeclampsia; aspirin; prophylaxis; high-risk pregnancies